Valuing the health benefits of active transport modes. - Genter, J. A.; Donovan, S.; Petrenas, B.; Badland, H. (My University, 2008)
The report seeks to provide a per-kilometre value for the health benefits of active transport modes (such as walking and cycling) that is compatible with the Land Transport New Zealand Economic Evaluation Manual Volume 2 (EEM2). The first two sections of the report begin by explaining the scope of the project and the background. Section 3 investigates the evidence of the connection between physical activity and health outcomes. Section 4 clarifies the role of active transport modes as physical activity, and reports the New Zealand-specific data about active transport mode engagement. Section 5 gives a brief comparative summary of the literature review of cost-benefit analyses and valuation techniques used overseas to value the health benefits of active modes.
Keywords: Individualverkehr; Fahrradverkehr; Fußgänger; Kosten-Nutzen-Analyse; Gesundheitsförderung; Fahrradfahren; Mobilitätsverhalten; Studie